2017
DOI: 10.3892/mmr.2017.7932
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthes�kirilowii extract enhances repair of UVB radiation‑induced DNA damage by regulating BMAL1 and miR‑142‑3p in human keratinocytes

Abstract: Ultraviolet B (UVB) radiation induces DNA damage, oxidative stress and inflammation, and suppresses the immune system in the skin, which collectively contribute to skin aging and carcinogenesis. The DNA damage response, including DNA repair, can be regulated by the circadian clock and microRNA (miRNA) expression. The aim of the present study was to evaluate the reparative action of Trichosanthes kirilowii extract (TKE) against UVB irradiation-induced DNA damage in human keratinocytes. TKE demonstrated low cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This leads to antioxidative effects in human skin. Furthermore, previous studies reported that the main plants ingredients in SHYBE exhibit various anti‐aging properties . The aqueous root extract Asparagus cochinchinensis showed antioxidant abilities as strong as vitamin C .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This leads to antioxidative effects in human skin. Furthermore, previous studies reported that the main plants ingredients in SHYBE exhibit various anti‐aging properties . The aqueous root extract Asparagus cochinchinensis showed antioxidant abilities as strong as vitamin C .…”
Section: Discussionmentioning
confidence: 98%
“…Astragalus membranceus increased hyaluronic acid content and cellular expression of telomerase reverse transcriptase . Trichosanthes kirilowii extract enhanced repair of ultraviolet radiation‑induced DNA damage by regulating BMAL1 and miR‑142‑3p in human keratinocytes . Glycyrrhiza glabra induced antioxidant enzymes and increased TNF‐γ, IL‐6, IL‐Iβ, NF‐kB, testosterone, and DHEA‐S levels …”
Section: Discussionmentioning
confidence: 99%
“…Recent study indicated that trichosanthes kirilowii, a traditional Chinese herb, exerted a protective role for the treatment of skin diseases via regulating the level of miR-142. 31 Previous studies indicated that some miRNAs play a vital role in the development of psoriasis, such as miR-125b-5p, miR-181b-5p, miR-187, miR-223, and miR- 744. 3,19,21,22 Our data indicated that triptolide had very limited effect on the levels of miR-125b-5p, miR-187, miR-223, and miR-744 in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data are representative of three or more independent experiments. **p < .01, ***p < .001, ****p < .0001 [Color figure can be viewed at wileyonlinelibrary.com] DNA damage can be induced by endogenous metabolites that can react with macromolecules, such as lipids, proteins or nucleic acids, and exogenous stimulants, such as ionizing radiation, ultraviolet radiation, and ROS (Babazadeh et al, 2012;Joo, Hong, Kim, & Choi, 2018;Kimeswenger et al, 2016;Salmon et al, 2004). It was found that vitrification increased ROS levels, which is consistent with our results that showed that oocyte vitrification enhanced ROS generation in MII oocytes and resulted in zygotes and two-cell embryos.…”
Section: Discussionmentioning
confidence: 99%